Autonomous Recognition System for Skin Pigment Evaluation. Issue 6 (2018) - Ondraczka, T.; Machacek, Z.; Koziorek, J.; Ondraczka, L.
Abstract: This paper deals with developing the software for skin pigment detection and evaluation by web camera. The methods of edge detection and mathematical morphology are used for skin pigment detection. Parameters are calculated by special methods. The parameters are evaluated by ABCD rule of skin pigment examination. Algorithm for skin pigment evaluation is based on fuzzy conditions. The software is designed for a dermatological ambulance, but it can be used as online software for patients to evaluate skin pigment from home only by using a web camera. This will dramatically decrease the number of patients on dermatological ambulances and speed up examination of the serious cases.